Answer:
y = 5
Explanation:
Simplifying
y + 6 = -3y + 26
Reorder the terms:
6 + y = -3y + 26
Reorder the terms:
6 + y = 26 + -3y
Solving
6 + y = 26 + -3y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '3y' to each side of the equation.
6 + y + 3y = 26 + -3y + 3y
Combine like terms: y + 3y = 4y
6 + 4y = 26 + -3y + 3y
Combine like terms: -3y + 3y = 0
6 + 4y = 26 + 0
6 + 4y = 26
Add '-6' to each side of the equation.
6 + -6 + 4y = 26 + -6
Combine like terms: 6 + -6 = 0
0 + 4y = 26 + -6
4y = 26 + -6
Combine like terms: 26 + -6 = 20
4y = 20
Divide each side by '4'.
y = 5
Simplifying
y = 5